Macroeconomics for MBAs and masters of finance - Davis, Morris A. 1972- (Cambridge University Press, 2009)
Using a rigorous and concise framework, this book teaches the foundations of modern macroeconomic theory and its methods. It is ideally suited for students taking a first graduate course in macroeconomics as part of an MBA, finance, or economics degree. The book explains recent advances of modern macroeconomic theory with respect to growth, business cycles, and asset pricing by focusing on aspects of firm and household behavior that are embedded in modern macroeconomic studies. Throughout the book data issues are discussed in detail: where to find the data, how to download it, and the correspondence of data with model predictions. The mathematical level assumes that students have taken a course in calculus. With its emphasis on dynamic inter-temporal macroeconomics and the use of data, the book provides students with a core toolkit that will equip them both for more advanced study and for professional careers as economists